Current Challenges and Advances in Atherosclerosis - Ishigami, Tomoaki (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint focuses on research on atherosclerosis. Atherosclerosis causes catastrophic thrombotic cardiovascular events, threatening not only individual healthy longevity but also socio-financial burden for the infrastructural emergent medical system. In the field of cardiovascular medicine, atherosclerosis has the largest number of patients and is an important disease that determines healthy life expectancy. There is currently no other way to control the disease than to maximize the use of medical resources and save lives. It has been clarified that local and systemic inflammation, along with risk factors, are closely related to the etiology of atherosclerosis.